A proteomic approach to identify metalloproteins and metal-binding proteins in liver from diabetic rats - Braga, Camila Pereira [UNESP]; Souza Vieira, Jose Cavalcante [UNESP]; Grove, Ryan A.; Boone, Cory H. T.; Leiter, Aline de Lima; Rabelo Buzalaf, Marilia Afonso; Henrique Fernandes, Ana Angelica [UNESP]; Adamec, Jiri; Padilha, Pedro de Magalhaes [UNESP] (Elsevier B.V., 2017)
Proteins play crucial roles in biological systems, thus studies comparing the protein pattern present in a healthy sample with an affected sample have been widely used for disease biomarker discovery. Although proteins containing metal ions constitute only a small proportion of the proteome, they are essential in a multitude of structural and functional processes. The correct association between metal ions and proteins is essential because this binding can significantly interfere with normal protein function. Employment of a metalloproteomic study of liver samples from diabetic rats permitted determination of the differential abundance of copper-, selenium-, zinc- and magnesium-associated proteins between diabetic, diabetic treatment with insulin and non-diabetic rats. Proteins were detected by ESI-MS/MS. Seventy-five different proteins were found with alterations in the metal ions of interest. The most prominent pathways affected under the diabetic model included: amino-acid metabolism and its derivates, glycogen storage, metabolism of carbohydrates, redox systems and glucose metabolism. Overall, the current methods employed yielded a greater understanding of metal binding and how type 1 diabetes and insulin treatment can modify some metal bonds in proteins, and therefore affect their mechanism of action and function. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Electrospray ionization-tandem mass spectrometry; Flame atomic absorption spectrometry; Graphite furnace atomic absorption spectrometry; Metalloproteomic; Type 1 diabetes; Two-dimensional electrophoresis